Silver-coated magnetic metal filler with magnetic field shielding effectiveness as well as preparation method and application of silver-coated magnetic metal filler
By using displacement reaction and electroless plating technology in electromagnetic shielding materials, silver nanoshell coated with magnetic metal is formed, which solves the problem of insufficient shielding performance of existing materials in low-frequency magnetic fields, and achieves efficient magnetic shielding effect.
Patent Information
- Application Number
- CN202411823702.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing electromagnetic shielding materials have limited effectiveness in low-frequency magnetic field shielding, and the preparation method of silver-clad magnetic metal powder is difficult to control the degree of oxidation.
The magnetic metal surface is uniformly activated by the replacement reaction, and electrochemical plating is performed using silver ammonia solution and reducing liquid to form a uniform silver nanoshell layer and coat the magnetic metal, thereby improving the magnetic permeability and eddy current loss of the material.
It realizes high shielding performance under low-frequency magnetic fields, avoids the impact of the oxide layer on the electromagnetic exchange between the magnetic core and the shell, and significantly improves the magnetic shielding performance of the material.
Smart Images

Figure CN119634726A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic shielding materials, and in particular to a silver-coated magnetic metal filler with magnetic field shielding effectiveness, a preparation method and application thereof. Background Art
[0002] With the continuous development of electronic technology and the increasing popularity of electronic equipment, the electromagnetic environment in modern society has become increasingly complex. The frequency of electromagnetic waves generated by various electronic devices can range from thousands of hertz to tens of gigahertz, which has a serious interference effect on the normal operation of electronic and electrical equipment. Therefore, it is necessary to use electromagnetic shielding materials to shield electromagnetic waves. The existing electromagnetic shielding materials are mainly various composite materials such as electromagnetic shielding rubber and electromagnetic shielding coatings. Such electromagnetic shielding composite materials are mainly composed of electromagnetic shielding fillers and matrix, and their shielding performance is determined by the electromagnetic shielding fillers. The electromagnetic shielding fillers used in existing commercial electromagnetic shielding composite materials are various conductive fillers, such as silver powder, graphite powder, carbon nanotubes, silver-coated copper, etc. Such materials have good shielding performance for plane waves in the megahertz band and gigahertz band. The field source distance r>λ / 2Π, the electromagnetic radiation is far-field radiation, and the electromagnetic wave appears as a uniform plane wave. At this time, electromagnetic shielding can be achieved by only losing one of the electric field or the magnetic field. The natural resonance frequency of magnetic materials is low, the impedance in the plane wave range is small, and the loss capacity of electromagnetic waves is weak; the skin depth of conductive materials decreases with the increase of frequency, and its loss capacity increases with the increase of frequency. On the whole, the most effective way to shield plane waves is to use conductive materials. When the field source distance r is less than λ / 2Π, the electromagnetic radiation is near-field radiation, and the electromagnetic wave exhibits quasi-static field characteristics. The design of electromagnetic shielding materials needs to take into account both electric field and magnetic field shielding. For magnetic fields, due to the weakening of the skin effect of conductive materials and the reduction of wave impedance, it is impossible to form a good shielding for the magnetic field, while magnetic conductive materials can achieve magnetic field shielding through loss mechanisms such as magnetic shunting and eddy current loss. However, for electromagnetic shielding composite materials, the distribution of magnetic conductive fillers in them determines their limited electrical conductivity and low eddy current loss, and their magnetic shielding effectiveness is often limited. In summary, magnetic field shielding is the focus and difficulty of electromagnetic shielding. It is difficult for a single conductive or magnetic electromagnetic shielding composite material to meet the electromagnetic shielding requirements of low-frequency magnetic fields.
[0003] Improving the eddy current loss of electromagnetic shielding fillers is the key to improving their low-frequency magnetic shielding effectiveness. In recent years, many studies and inventions have improved the eddy current loss of electromagnetic shielding fillers by compounding magnetic conductive materials with conductive materials. The prior art discloses a silver-plated Fe3O4 powder, which has a low magnetic permeability on the one hand, and on the other hand, Fe3O4 itself does not have conductivity, and it is difficult to form a conductive path with the silver shell layer to enhance eddy current loss. The prior art also discloses an electromagnetic shielding filler composited with nickel and expanded graphite, which has high shielding effectiveness in the range of 300kHz-1.5MHz. However, the limited magnetic permeability and electrical conductivity of nickel and expanded graphite limit the further improvement of its electromagnetic shielding effectiveness. Therefore, it is urgent to develop an electromagnetic composite electromagnetic shielding filler that can achieve good low-frequency magnetic field shielding. Summary of the invention
[0004] In view of the deficiencies in the above-mentioned background technology, the present invention mainly solves the problem that the preparation of silver-coated magnetic metal powder used for broadband electromagnetic shielding and its oxidation degree are difficult to control in the prior art. The present invention provides a silver-coated magnetic metal filler with magnetic field shielding effectiveness and its preparation method and application. The method utilizes a replacement reaction to uniformly activate the surface of the magnetic metal, and further realizes uniform coating of the silver layer. Silver and magnetic metals have good electrical conductivity. The prepared silver-coated magnetic metal can form a good conductive network, and the magnetic core can improve the magnetic permeability of the material, thereby improving the eddy current loss of the electromagnetic shielding filler, and finally achieving high shielding effectiveness under low-frequency magnetic fields.
[0005] The first object of the present invention is to provide a method for preparing a silver-coated magnetic metal filler having magnetic field shielding effectiveness, comprising the following steps: The magnetic metal powder is acid-washed to obtain acidified magnetic metal powder; The acidified magnetic metal powder is added to the silver nitrate solution, and then grease is added, followed by stirring and reacting to obtain the activated magnetic metal powder; The activated magnetic metal powder, reducing solution and silver ammonia solution are uniformly mixed, and then grease is added, and stirred to react to obtain a silver-coated magnetic metal filler with magnetic field shielding efficiency; The reducing liquid is prepared from a certain amount of dispersant, reducing agent and deionized water.
[0006] Preferably, the magnetic metal powder is one or more of iron-silicon-aluminum alloy, iron-silicon-chromium alloy, iron-silicon alloy, carbonyl iron, carbonyl nickel, iron-aluminum-boron alloy, iron-boron-phosphorus alloy, iron-nickel-molybdenum alloy, iron-chromium-nickel alloy, iron-nickel alloy, iron-cobalt-chromium alloy, and iron-cobalt-nickel-chromium alloy; The magnetic metal powder is spherical or flake in shape, and has a particle size of 4-42 μm.
[0007] Preferably, the silver nitrate solution is prepared by dissolving silver nitrate in a water solvent; The concentration of the silver nitrate solution is 0.5-10 g / L; The mass ratio of the acidified magnetic metal powder to silver nitrate is 10:0.1-3.
[0008] Preferably, during the preparation process of the activated magnetic metal powder, the reaction temperature is 30-45° C. and the reaction time is 0.5-3 h.
[0009] Preferably, the oil is one or more of cocoa butter, coconut oil, kerosene and paraffin oil.
[0010] Preferably, the dispersant is one or more of gelatin, polymethylpyrrolidone, OP-10, and sodium dodecylbenzene sulfonate; and the reducing agent is one or more of glucose, formaldehyde solution, hydrazine hydrate, and potassium sodium tartrate.
[0011] Preferably, the silver ammonia solution is prepared by dispersing silver nitrate and ammonia water in an aqueous solvent, wherein the concentration of the silver ammonia solution is 0.5-20 g / L, and the molar ratio of silver nitrate to ammonia water in the silver ammonia solution is 1:1.05-2.
[0012] Preferably, the pickling of the magnetic metal powder comprises: Mix the magnetic metal powder with dilute sulfuric acid and stir for 2-6 minutes. Then use a magnet to adsorb the magnetic metal powder to the bottom of the container and pour out the supernatant. Wash the precipitate with deionized water until the pH of the supernatant is 6.5-7.5. The concentration of the dilute sulfuric acid is 4-6wt%.
[0013] The second object of the present invention is to provide a silver-coated magnetic metal filler having magnetic field shielding effectiveness.
[0014] The third object of the present invention is to provide a silver-coated magnetic metal filler with magnetic field shielding effectiveness for use in electromagnetic shielding.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a silver-coated magnetic metal filler with magnetic field shielding effectiveness, and a preparation method and application thereof. The present invention uses a replacement reaction to uniformly activate the surface of the magnetic metal based on the chemical properties of the magnetic metal, and further realizes uniform coating of the silver layer. Silver and magnetic metals have good electrical conductivity. The prepared silver-coated magnetic metal can form a good conductive network. The magnetic core can improve the magnetic permeability of the material, thereby improving the eddy current loss of the electromagnetic shielding filler, and ultimately achieving high shielding effectiveness under low-frequency magnetic fields. Lightweight and inert grease is used to avoid oxidation during replacement activation or chemical silver plating of the magnetic metal, so that the electromagnetic exchange between the magnetic core and the conductive shell is significantly enhanced, further improving its shielding effectiveness. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The time and photos of the samples of each embodiment and comparative example when a large number of bubbles appeared are shown.
[0017] Figure 2 Surface conductivity of Examples 1-2 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.
[0019] The object of the present invention is to provide an electromagnetically composite electromagnetic shielding filler which can achieve good low-frequency magnetic field shielding.
[0020] In order to achieve the above object, the present invention provides a method for preparing a silver-coated magnetic metal filler having magnetic field shielding effectiveness in a first aspect, comprising the following steps: The magnetic metal powder is acid-washed to obtain acidified magnetic metal powder; The acidified magnetic metal powder is added to the silver nitrate solution, and then grease is added, followed by stirring and reacting to obtain the activated magnetic metal powder; The activated magnetic metal powder, reducing solution and silver ammonia solution are uniformly mixed, and then grease is added, and stirred to react to obtain a silver-coated magnetic metal filler with magnetic field shielding efficiency; The reducing liquid is prepared from a certain amount of dispersant, reducing agent and deionized water.
[0021] The invention is based on the fact that the original magnetic metal powder has an oxide layer on its surface, which will affect the adhesion of subsequent plating layers on the one hand, and weaken the electromagnetic coupling between the magnetic core and the shell layer on the other hand. The oxide layer on the surface of the magnetic metal powder can be effectively removed after acid washing; silver nitrate will undergo a replacement reaction with the acidified magnetic metal powder to generate silver clusters or silver particles of several to tens of nanometers on the surface of the magnetic metal, so that the silver layer in the subsequent chemical plating process can be formed on its surface; finally, through chemical plating, a silver nanoshell layer is prepared in situ on the surface of the magnetic metal by utilizing a reduction reaction between a silver ammonia solution and a reducing solution, thereby obtaining a silver-coated magnetic metal powder.
[0022] The magnetic metal powder is one or more of iron-silicon-aluminum alloy, iron-silicon-chromium alloy, iron-silicon alloy, carbonyl iron, carbonyl nickel, iron-aluminum-boron alloy, iron-boron-phosphorus alloy, iron-nickel-molybdenum alloy, iron-chromium-nickel alloy, iron-nickel alloy, iron-cobalt-chromium alloy, and iron-cobalt-nickel-chromium alloy; The magnetic metal powder is spherical or flake in shape, and has a particle size of 4-42 μm.
[0023] The silver nitrate solution is prepared by dissolving silver nitrate in a water solvent; The concentration of the silver nitrate solution is 0.5-10 g / L; The mass ratio of the acidified magnetic metal powder to silver nitrate is 10:0.1-3.
[0024] During the preparation process of the activated magnetic metal powder, the reaction temperature is 30-45° C. and the reaction time is 0.5-3 h.
[0025] The oil is one or more of cocoa butter, coconut oil, kerosene and paraffin oil.
[0026] The dispersant is one or more of gelatin, polymethylpyrrolidone, OP-10, and sodium dodecylbenzene sulfonate; the reducing agent is one or more of glucose, formaldehyde solution, hydrazine hydrate, and potassium sodium tartrate.
[0027] The silver ammonia solution is prepared by dispersing silver nitrate and ammonia water in a water solvent, wherein the concentration of the silver ammonia solution is 0.5-20 g / L, and the amount ratio of silver nitrate to ammonia water in the silver ammonia solution is 1:1.05-2.
[0028] When the magnetic metal powder is pickled, it includes: Mix the magnetic metal powder with dilute sulfuric acid and stir for 2-6 minutes. Then use a magnet to adsorb the magnetic metal powder to the bottom of the container and pour out the supernatant. Wash the precipitate with deionized water until the pH of the supernatant is 6.5-7.5. The concentration of the dilute sulfuric acid is 4-6 wt %.
[0029] In one embodiment, a method for preparing a silver-coated magnetic metal filler having magnetic field shielding effectiveness comprises: (1) Pickling: Mix the magnetic metal powder with dilute sulfuric acid and stir continuously with a rotary stirrer. After stirring for a certain period of time, use a magnet to adsorb the magnetic metal powder to the bottom of the container and pour out the supernatant. Wash the precipitate with deionized water until the pH of the supernatant is 7; (2) Replacement activation: Mix the magnetic metal powder with a certain amount of silver nitrate solution, add a certain amount of oil, stir and react at a certain temperature, and pour off the supernatant after a certain period of reaction. In this step, the mass ratio of silver nitrate solution to oil is 5-20:1; (3) Chemical silver plating: a certain amount of dispersant, reducing agent and deionized water are prepared into a reducing solution, the metal powder, reducing solution and silver ammonia solution are mixed in a certain manner, and a certain amount of grease is added, and the reaction is stirred at a certain temperature. When there are no residual silver particles in the solution, the solution is filtered, washed and vacuum dried to obtain a silver-coated magnetic metal filler, wherein the mass ratio of the silver ammonia solution to the grease in this step is 2.5~15:1.
[0030] The magnetic metal powder has a spherical or flaky morphology, and an equivalent average particle size of the magnetic metal powder is 4-42 μm.
[0031] The pickling time is 2 to 4 minutes. When the magnetic metal powder is a high-passivation system alloy, the pickling time can be extended to 6 minutes.
[0032] In the replacement activation step, the mass ratio of magnetic metal powder to silver nitrate is 10:0.1-3, and the concentration of silver nitrate solution is 0.5-10 g / L.
[0033] The replacement activation temperature is 30-45° C., and the reaction time is 0.5-3 h.
[0034] The stirring speed in the displacement activation and chemical silver plating steps is 80-150 rpm.
[0035] The magnetic metal powder, reducing solution and silver ammonia solution are mixed in the following manner: the magnetic metal powder is dispersed in the silver ammonia solution, and then the reducing solution is dripped or poured into the solution.
[0036] Specifically, the magnetic metals are iron-silicon-aluminum alloy, iron-silicon-chromium alloy, iron-silicon alloy, carbonyl iron, carbonyl nickel, iron-nickel-molybdenum alloy, iron-chromium-nickel alloy, iron-nickel alloy, iron-cobalt-chromium alloy, and iron-cobalt-nickel-chromium alloy, all of which are products of Ganzhou Blue Ocean New Materials Co., Ltd.
[0037] Silver nitrate is a transparent crystalline powder produced by Shanghai Hushi Laboratory Equipment Co., Ltd.
[0038] The dispersant is one or more of gelatin, PVP, OP-10, and SDBS, wherein gelatin is a white powder, PVP is a fine white powder, OP-10 is a white and milky white paste, and SDBS is a light yellow powder, all of which are products of Shanghai Roche Pharmaceuticals Co., Ltd.
[0039] The oil is one of cocoa butter, coconut oil, kerosene and paraffin oil, among which cocoa butter is a light yellow thick liquid, coconut oil is a white viscous liquid, kerosene is a light yellow oily liquid, and paraffin oil is a light yellow oily liquid, all of which are from Jiangsu Saipahan Energy Technology.
[0040] The reducing agents are glucose, formaldehyde solution, hydrazine hydrate, and potassium sodium tartrate. Glucose is one or more white powders. The formaldehyde solution has a concentration of 50wt.%, which is a colorless solution with a pungent odor. Hydrazine hydrate is a colorless fuming liquid. Potassium sodium tartrate is a transparent crystalline powder. All of them are products of Sinopharm Chemical Reagent Co., Ltd.
[0041] A second aspect of the present invention provides a silver-coated magnetic metal filler having magnetic field shielding effectiveness.
[0042] A third aspect of the present invention provides an application of a silver-coated magnetic metal filler having magnetic field shielding effectiveness in electromagnetic shielding.
[0043] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.
[0044] Example 1 Add 200 mL of 5 wt% dilute sulfuric acid to 10 g of carbonyl nickel powder and stir mechanically for 8 min. After acidification, pour in a large amount of deionized water to dilute to pH = 7 neutral, and filter to obtain the acidified carbonyl nickel powder. Weigh 1g AgNO3 and dissolve it in 150mL water, then add 1g PVP and the obtained acidified carbonyl nickel powder, disperse all the reactants evenly, pour in 20g kerosene and stir mechanically at a speed of 120rpm, the water bath temperature is 40℃, react for 30min, after the replacement reaction is completed, pour off the upper turbid liquid to obtain the activated carbonyl nickel powder; Weigh 6.35 g of glucose and dissolve it in 350 mL of deionized water, and add 1 g of PVP to obtain a reduced solution; Weigh 6 g of AgNO3 and dissolve it in 300 mL of deionized water. Add ammonia water until it becomes clear to prepare a silver ammonia solution. The activated carbonyl nickel powder is mixed with the silver ammonia solution, 20g of kerosene is added, and the mixture is placed in a 40°C water bath and mechanically stirred at a speed of 120rpm; the reducing solution is added dropwise to the reaction system at a rate of 100mL / h using a syringe pump, and the end of the delivery tube should be fixed below the grease layer during the addition; after the injection is completed, the reaction is allowed to continue for 30min, and then a sodium chloride solution is used to detect whether there are silver particles remaining in the supernatant. If so, the reaction is continued until the silver particles in the supernatant react completely, the supernatant is poured out, and the mixture is washed to neutrality with deionized water, and then the silver-coated nickel powder is obtained after vacuum drying.
[0045] Example 2 200 mL of 5 wt% dilute sulfuric acid was added to 10 g of iron, silicon and chromium powder and mechanically stirred for 4 minutes. After acidification, a large amount of deionized water was added to dilute to neutrality and the acidified iron, silicon and chromium powder was obtained after filtration.
[0046] Weigh 0.8g AgNO3 and dissolve it in 120mL water, then add 1g OP-10 and the acidified iron, silicon and chromium powder. After all the reactants are evenly dispersed, pour in 20g coconut oil and stir mechanically at a speed of 120rpm. The water bath temperature is 40℃ and the reaction is carried out for 40 minutes. After the replacement reaction is completed, the upper turbid liquid is poured off to obtain the activated iron, silicon and chromium powder. Weigh 20 mL of formaldehyde solution and dissolve it in 300 mL of deionized water, and add 1 g of OP-10 to obtain a reducing solution; Weigh 5 g of AgNO3 and dissolve it in 260 mL of deionized water. Add ammonia water until the solution becomes clear to prepare a silver ammonia solution. The activated iron-silicon-chromium powder is mixed with the silver-ammonia solution, 20 g of kerosene is added, and the mixture is placed in a 40°C water bath and mechanically stirred at a speed of 120 rpm; the reducing solution is added dropwise to the reaction system at a rate of 100 mL / h using a syringe pump, and the end of the delivery tube should be fixed below the grease layer during the addition; after the injection is completed, the reaction is allowed to continue for 30 minutes, and then a sodium chloride solution is used to detect whether there are any silver particles remaining in the supernatant. If so, the reaction is continued until the silver particles in the supernatant are completely reacted, the supernatant is discarded, and the mixture is washed to neutrality with deionized water, and then the silver-coated iron-silicon-chromium powder is obtained after vacuum drying.
[0047] Example 3 Add 200 mL of 5 wt% dilute sulfuric acid to 10 g of sendust powder and stir mechanically for 3 minutes. After acidification, pour in a large amount of deionized water to dilute to neutrality, and filter to obtain the acidified sendust powder.
[0048] Weigh 1.0g AgNO3 and dissolve it in 200mL water, then add 1g gelatin and the acidified sendustine powder. After all the reactants are evenly dispersed, pour in 20g cocoa butter and stir mechanically at 100rpm. The water bath temperature is 40℃ and the reaction is carried out for 40 minutes. After the replacement reaction is completed, pour off the upper turbid liquid to obtain the cremated sendustine powder.
[0049] Weigh 7.5 g glucose and 0.75 g potassium sodium tartrate and dissolve them in 420 mL of deionized water, and add 1 g gelatin to obtain a reduced solution; Weigh 6 g of AgNO3 and dissolve it in 340 mL of deionized water. Add ammonia water until the solution becomes clear to prepare a silver ammonia solution. The activated iron-silicon-aluminum powder is mixed with the silver-ammonia solution, 20 g of kerosene is added, and the mixture is placed in a 40°C water bath and mechanically stirred at a speed of 100 rpm; the reducing liquid is added dropwise to the reaction system at a rate of 100 mL / h using a syringe pump, and the end of the delivery tube should be fixed below the grease layer during the addition; after the injection is completed, the reaction is allowed to continue for 30 minutes, and then a sodium chloride solution is used to detect whether there are any silver particles remaining in the supernatant. If so, the reaction is continued until the silver particles in the supernatant react completely, the supernatant is discarded, and the mixture is washed to neutrality with deionized water, and then the silver-coated iron-silicon-aluminum powder is obtained after vacuum drying.
[0050] Example 4 200 mL of 5 wt% dilute sulfuric acid was added to 10 g of carbonyl iron powder and mechanically stirred for 3 min. After acidification, a large amount of deionized water was added to dilute to neutrality and the acidified carbonyl iron powder was obtained after filtration.
[0051] Weigh 1.5g AgNO3 and dissolve it in 300mL water, then add 1g SDBS and the acidified carbonyl iron powder. After all the reactants are evenly dispersed, pour in 20g cocoa butter and stir mechanically at 150rpm. The water bath temperature is 40℃ and the reaction is carried out for 40min. After the replacement reaction is completed, pour off the upper turbid liquid to obtain the activated carbonyl iron powder.
[0052] Weigh 7.5 g glucose and 0.75 g potassium sodium tartrate and dissolve them in 420 mL of deionized water, and add 1 g gelatin to obtain a reduced solution; Weigh 6 g of AgNO3 and dissolve it in 340 mL of deionized water. Add ammonia water until the solution becomes clear to prepare a silver ammonia solution. The activated carbonyl iron powder is mixed with the silver ammonia solution, 20 g of kerosene is added, and the mixture is placed in a 42°C water bath and mechanically stirred at a speed of 150 rpm; the reducing solution is added dropwise to the reaction system at a rate of 100 mL / h using a syringe pump, and the end of the delivery tube should be fixed below the grease layer during the addition; after the injection is completed, the reaction is allowed to continue for 30 minutes, and then a sodium chloride solution is used to detect whether there are residual silver particles in the supernatant. If so, the reaction is continued until the silver particles in the supernatant react completely, the supernatant is discarded, and the mixture is washed to neutrality with deionized water, and the silver-coated carbonyl iron powder is obtained after vacuum drying.
[0053] Example 5 200 mL of 5 wt% dilute sulfuric acid was added to 10 g of iron-nickel-molybdenum powder and mechanically stirred for 6 min. After acidification, a large amount of deionized water was added to dilute to neutrality, and the acidified iron-nickel-molybdenum powder was obtained after filtration.
[0054] Weigh 1.2g AgNO3 and dissolve it in 120mL water, then add 1g OP-10 and the acidified carbonyl nickel powder. After all the reactants are evenly dispersed, pour in 20g cocoa butter and stir mechanically at 150rpm. The water bath temperature is 42℃ and the reaction is carried out for 90min. After the replacement reaction is completed, pour off the upper turbid liquid to obtain the activated iron-nickel-molybdenum powder.
[0055] Weigh 3 g of hydrazine hydrate and dissolve it in 350 mL of deionized water, and add 1 g of OP-10 to obtain a reducing solution; Weigh 5.4 g of AgNO3 and dissolve it in 270 mL of deionized water. Add ammonia water until the solution becomes clear to prepare a silver ammonia solution. The activated iron-nickel-molybdenum powder is mixed with the silver-ammonia solution, 20 g of kerosene is added, and the mixture is placed in a 42°C water bath and mechanically stirred at a speed of 150 rpm; the reducing liquid is added dropwise to the reaction system at a rate of 100 mL / h using a syringe pump, and the end of the delivery tube should be fixed below the grease layer during the addition; after the injection is completed, the reaction is allowed to continue for 30 minutes, and then a sodium chloride solution is used to detect whether there are residual silver particles in the supernatant. If so, the reaction is continued until the silver particles in the supernatant react completely, the supernatant is discarded, and the mixture is washed to neutrality with deionized water, and then vacuum dried to obtain silver-coated iron-nickel-molybdenum powder.
[0056] Example 6 200 mL of 5 wt% dilute sulfuric acid was added to 10 g of iron-silicon alloy powder and mechanically stirred for 3 min. After acidification, a large amount of deionized water was poured in to dilute to neutrality, and the acidified iron-silicon alloy powder was obtained after filtration.
[0057] Weigh 1g AgNO3 and dissolve it in 150mL water, then add 1g PVP and the acidified iron-silicon alloy powder. After all the reactants are evenly dispersed, pour in 20g coconut oil and stir mechanically at 90rpm. The water bath temperature is 38℃ and the reaction is carried out for 90min. After the replacement reaction is completed, pour off the upper turbid liquid to obtain the activated iron-silicon alloy powder.
[0058] Weigh 9.53 g of glucose and dissolve it in 350 mL of deionized water, and add 1 g of PVP to obtain a reducing solution; Weigh 5 g of AgNO3 and dissolve it in 300 mL of deionized water. Add ammonia water until it becomes clear to prepare a silver ammonia solution. The activated iron-silicon alloy powder is mixed with the silver-ammonia solution, 20 g of coconut oil is added, and the mixture is placed in a 38°C water bath and mechanically stirred at a speed of 90 rpm; the reducing liquid is added dropwise to the reaction system at a rate of 200 mL / h using a syringe pump, and the end of the delivery tube should be fixed below the oil layer during the addition; after the injection is completed, the reaction is allowed to continue for 30 minutes, and then a sodium chloride solution is used to detect whether there are any silver particles remaining in the supernatant. If so, the reaction is continued until the silver particles in the supernatant react completely, the supernatant is discarded, and the mixture is washed to neutrality with deionized water, and then vacuum dried to obtain the silver-coated iron-silicon alloy powder.
[0059] Example 7 Add 200 mL of 5 wt% dilute sulfuric acid to 10 g of Fe-Cr-Ni alloy powder and stir mechanically for 6 min. After acidification, pour in a large amount of deionized water to dilute to neutrality, and filter to obtain the acidified Fe-Cr-Ni alloy powder; Weigh 1g AgNO3 and dissolve it in 150mL water, then add 1g PVP and the acidified iron-chromium-nickel alloy powder, disperse all the reactants evenly, pour in 20g coconut oil and stir mechanically at a speed of 90rpm, the water bath temperature is 38℃, react for 90min, after the replacement reaction is completed, pour off the upper turbid liquid to obtain the activated iron-chromium-nickel alloy powder; Weigh 9.53 g of glucose and dissolve it in 350 mL of deionized water, and add 1 g of PVP to obtain a reducing solution; Weigh 5 g of AgNO3 and dissolve it in 300 mL of deionized water. Add ammonia water until it becomes clear to prepare a silver ammonia solution. The activated iron-chromium-nickel alloy powder is mixed with the silver-ammonia solution, 20 g of coconut oil is added, and the mixture is placed in a 38°C water bath and mechanically stirred at a speed of 90 rpm; the reducing liquid is added dropwise to the reaction system at a rate of 200 mL / h using a syringe pump, and the end of the delivery tube should be fixed below the grease layer during the addition; after the injection is completed, the reaction is allowed to continue for 30 minutes, and then a sodium chloride solution is used to detect whether there are silver particles remaining in the supernatant. If so, the reaction is continued until the silver particles in the supernatant react completely, the supernatant is poured out, and the mixture is washed to neutrality with deionized water, and the silver-coated iron-chromium-nickel alloy powder is obtained after vacuum drying.
[0060] Example 8 Add 200 mL of 5 wt% dilute sulfuric acid to 10 g of iron-cobalt-chromium alloy powder and stir mechanically for 6 minutes. After acidification, pour in a large amount of deionized water to dilute to neutrality, and filter to obtain the acidified iron-cobalt-chromium alloy powder; Weigh 1.2g AgNO3 and dissolve it in 210mL water, then add 0.8g PVP and the acidified iron-cobalt-chromium alloy powder, disperse all the reactants evenly, pour in 20g paraffin oil and stir mechanically at a speed of 110rpm, the water bath temperature is 40℃, react for 180min, after the replacement reaction is completed, pour off the upper turbid liquid, and obtain the activated iron-cobalt-chromium alloy powder; Weigh 7.62 g of sodium potassium tartrate and dissolve it in 340 mL of deionized water, and add 0.8 g of PVP to obtain a reducing solution; Weigh 5 g of AgNO3 and dissolve it in 300 mL of deionized water. Add ammonia water until it becomes clear to prepare a silver ammonia solution. The activated iron-cobalt-chromium alloy powder is mixed with the silver-ammonia solution, 20 g of paraffin oil is added, and the mixture is placed in a 40°C water bath and mechanically stirred at a speed of 110 rpm; the reducing solution is then poured into the mixture, and a funnel is used for drainage, and the lower end of the funnel should be immersed below the grease layer. The reaction is continued for 30 minutes, and then a sodium chloride solution is used to detect whether there are residual silver particles in the supernatant. If so, the reaction is continued until the silver particles in the supernatant are completely reacted, the supernatant is discarded, and the mixture is washed with deionized water until neutral. After vacuum drying, the silver-coated iron-cobalt-chromium alloy powder is obtained.
[0061] Example 9 Add 200 mL of diluted sulfuric acid (7 wt%) to 10 g of iron-cobalt-nickel-chromium alloy powder and stir mechanically for 6 minutes. After acidification, pour in a large amount of deionized water to dilute to neutrality, and filter to obtain the acidified iron-cobalt-nickel-chromium alloy powder; Weigh 1g AgNO3 and dissolve it in 150mL water, then add 1.0g PVP and the acidified iron-cobalt-nickel-chromium alloy powder, disperse all the reactants evenly, pour in 20g kerosene and stir mechanically at a speed of 130rpm, the water bath temperature is 40℃, react for 180min, after the replacement reaction is completed, pour off the upper turbid liquid to obtain the activated iron-cobalt-nickel-chromium alloy powder; Weigh 8.5 g of glucose and dissolve it in 340 mL of deionized water, and add 1.0 g of PVP to obtain a reduced solution; Weigh 6.35 g of AgNO3 and dissolve it in 270 mL of deionized water. Add ammonia water dropwise until the solution becomes clear to prepare a silver ammonia solution. The activated iron-cobalt-nickel-chromium alloy powder is mixed with the silver-ammonia solution, 20 g of kerosene is added, and the mixture is placed in a 40°C water bath and mechanically stirred at a speed of 130 rpm; the reducing solution is then poured into the mixture, and a funnel is used for drainage, and the lower end of the funnel should be immersed below the grease layer. The reaction is continued for 30 minutes, and then a sodium chloride solution is used to detect whether there are any silver particles remaining in the supernatant. If so, the reaction is continued until the silver particles in the supernatant are completely reacted, the supernatant is poured out, and the mixture is washed to neutrality with deionized water. After vacuum drying, the silver-coated iron-cobalt-nickel-chromium powder is obtained.
[0062] Example 10 Add 200 mL of 5 wt% dilute sulfuric acid to 10 g of iron-nickel alloy powder and stir mechanically for 6 minutes. After acidification, pour in a large amount of deionized water to dilute to neutrality, and filter to obtain the acidified iron-nickel alloy powder; Weigh 0.5g AgNO3 and dissolve it in 150mL water, then add 1.0g PVP and the acidified iron-nickel alloy powder, disperse all the reactants evenly, pour in 20g paraffin oil and stir mechanically at a speed of 100rpm, the water bath temperature is 40℃, react for 120min, and after the replacement reaction is completed, pour off the upper turbid liquid to obtain the activated iron-nickel alloy powder; Weigh 12.10 g of glucose and dissolve it in 450 mL of deionized water, and add 1.0 g of PVP to obtain a reducing solution; Weigh 5.8 g of AgNO3 and dissolve it in 410 mL of deionized water. Add ammonia water dropwise until the solution becomes clear to prepare a silver ammonia solution. The activated iron-nickel alloy powder is mixed with the silver-ammonia solution, 20 g of paraffin oil is added, and the mixture is placed in a 40°C water bath and mechanically stirred at a speed of 100 rpm; the reducing solution is then poured into the mixture, and a funnel is used for drainage, and the lower end of the funnel should be immersed below the grease layer. The reaction is continued for 30 minutes, and then a sodium chloride solution is used to detect whether there are any silver particles remaining in the supernatant. If so, the reaction is continued until the silver particles in the supernatant are completely reacted, the supernatant is poured out, and the mixture is washed to neutrality with deionized water. After vacuum drying, the silver-coated iron-nickel alloy powder is obtained.
[0063] In order to illustrate the performance of the silver-coated magnetic metal powder, the silver-coated magnetic metal powder prepared in each embodiment is mixed with an organic silicone resin to prepare a coating, and the corresponding coating is prepared by air compression spraying technology. The specific method is as follows: 70 parts of silver-coated magnetic metal powder, 25 parts of silicone resin, and 5 parts of polyamide curing agent were dispersed at 3000 rpm for 15 minutes using a stirring disperser, and then a certain amount of xylene was added to adjust the coating viscosity to 20-25 mPa·s, and stirring was continued at 3000 rpm for 15 minutes to obtain an electromagnetic shielding coating.
[0064] The organic silicon resin is a transparent viscous liquid, and is a product of Hubei Xinsihai Chemical Co., Ltd.
[0065] The polyamide curing agent is a medium-viscosity brown-yellow liquid, and is a product of Hubei Xinsihai Chemical Co., Ltd.
[0066] The xylene is a colorless transparent liquid with a special odor of aromatic hydrocarbons and is a product of Nanjing Hecheng Chemical Co., Ltd.
[0067] Subsequently, an electromagnetic shielding coating with a thickness of 1 mm was prepared by compressed air spraying. The specific method is as follows: pour the coating into a W-71 spray gun, adjust the spraying pressure to 0.5 MPa, the spraying distance to 15-20 cm, the spray gun moving speed to 30-40 cm / s, and spray evenly on the surface of the substrate in an S-shaped path; after each 0.1 mm coating is sprayed, the sample is dried at room temperature for 10 to 15 minutes, and then the sample is placed in an oven and kept at 80°C for 12 hours to solidify the coating sprayed on the surface of the substrate, and the preparation process is repeated until the thickness of the obtained prefabricated layer reaches 1.5 mm.
[0068] In order to further illustrate the protective effect of the light inert grease layer on the magnetic core during the material preparation process, two comparative examples are used for comparison and demonstration.
[0069] Comparative Example 1 Comparative Example 1 is prepared in the same manner as Example 1, but light inert grease is not added for protection during the preparation process. The specific preparation method is as follows: 200 mL of 5 wt% dilute sulfuric acid is added to 10 g of carbonyl nickel powder and mechanically stirred for 8 minutes. After acidification, a large amount of deionized water is poured in to dilute to neutrality, and the acidified carbonyl nickel powder is obtained after filtration.
[0070] Weigh 1g AgNO3 and dissolve it in 150mL water, then add 1g PVP and the obtained acidified carbonyl nickel powder, disperse all the reactants evenly, stir mechanically at a speed of 120rpm, set the water bath temperature at 40℃, react for 30min, after the replacement reaction is completed, pour off the upper turbid liquid to obtain the activated carbonyl nickel powder; Weigh 6.35 g of glucose and dissolve it in 350 mL of deionized water, and add 1 g of PVP to obtain a reduced solution; Weigh 6 g of AgNO3 and dissolve it in 300 mL of deionized water. Add ammonia water until it becomes clear to prepare a silver ammonia solution. The activated carbonyl nickel powder was mixed with the silver ammonia solution, placed in a 40°C water bath and mechanically stirred at a speed of 120 rpm; the reducing solution was added dropwise to the reaction system at a rate of 100 mL / h using a syringe pump, and the end of the delivery tube should be fixed below the grease layer during the addition; after the injection was completed, the reaction was allowed to continue for 30 minutes, and then a sodium chloride solution was used to detect whether there were any silver particles remaining in the supernatant. If so, the reaction was continued until the silver particles in the supernatant reacted completely, the supernatant was poured out, and the powder was washed with deionized water until neutral. After vacuum drying, the silver-coated carbonyl nickel powder was obtained, and then the silver-coated carbonyl nickel powder provided in Comparative Example 1 was used to prepare an electromagnetic shielding coating using the same preparation process as that in Example 1.
[0071] Comparative Example 2 Comparative Example 2 is prepared in the same manner as Example 2, but light inert grease is not added for protection during the preparation process. The specific preparation method is as follows: 200 mL of 5 wt% dilute sulfuric acid is added to 10 g of iron silicon chromium powder and mechanically stirred for 4 minutes. After acidification, a large amount of deionized water is poured in to dilute to neutrality, and the acidified iron silicon chromium powder is obtained after filtration; Weigh 0.8g AgNO3 and dissolve it in 120mL water, then add 1g OP-10 and the obtained acidified iron, silicon and chromium powder, disperse all the reactants evenly, pour in 20g coconut oil and stir mechanically at a speed of 120rpm, the water bath temperature is 40℃, react for 40min, after the replacement reaction is completed, pour off the upper turbid liquid to obtain the activated iron, silicon and chromium powder; Weigh 20 mL of formaldehyde solution and dissolve it in 300 mL of deionized water, and add 1 g of OP-10 to obtain a reducing solution; Weigh 5 g of AgNO3 and dissolve it in 260 mL of deionized water. Add ammonia water until the solution becomes clear to prepare a silver ammonia solution. The activated iron-silicon-chromium powder was mixed with the silver-ammonia solution, placed in a 40°C water bath and mechanically stirred at 120 rpm; the reducing solution was added dropwise to the reaction system at a rate of 100 mL / h using an injection pump, and the end of the delivery tube should be fixed below the grease layer during the addition; after the injection was completed, the reaction was allowed to continue for 30 minutes, and then a sodium chloride solution was used to detect whether there were any silver particles remaining in the supernatant. If so, the reaction was continued until the silver particles in the supernatant reacted completely, the supernatant was discarded, and the powder was washed with deionized water until neutral. The silver-coated iron-silicon-chromium powder was obtained after vacuum drying, and then the silver-coated iron-silicon-chromium powder provided in Comparative Example 2 was used to prepare an electromagnetic shielding coating using the same preparation process as that in Example 2.
[0072] To illustrate the shielding performance of the silver-coated magnetic metal coating prepared in the embodiment of the present invention, the magnetic shielding effectiveness of the silver-coated magnetic metal coating was tested by a shielded room method using a loop antenna in accordance with GB / T 30142-2013 “Test method for shielding effectiveness of planar electromagnetic shielding materials”. The specific results are shown in Table 1 below.
[0073] Table 1 Magnetic shielding effectiveness of various embodiments within 200kHz-30MHz
[0074] It can be seen from Table 1 that the silver-clad magnetic metal coating prepared in the embodiment of the present invention has an excellent magnetic shielding effect on electromagnetic waves in the 200kHz-30MHz band, and its magnetic shielding efficiency value is higher than 20dB, which meets the use requirements of civil electromagnetic shielding materials.
[0075] In order to further illustrate the protective effect of the light inert grease layer on the magnetic core during the material preparation process in the present invention, Examples 1 and 2 are compared and analyzed with Comparative Examples 1 and 2. First, the oxidation degree of the silver-coated magnetic metal filler is determined by the acid washing method. The specific method is as follows: 2 g of the prepared silver-coated metal filler is put into a vial, and then 20 mL of dilute hydrochloric acid (pH = 4) is poured in and the timing is started. The time when a large number of bubbles appear in the mixture in the bottle is recorded and photographed. The results are as follows: Figure 1 As shown. The hydrochloric acid solution will first react with the oxide layer on the surface of the silver-coated metal filler to generate water and metal ions. No bubbles will be generated in this process. When the oxide layer is completely corroded by the hydrochloric acid solution, the metal inside will undergo a replacement reaction with the hydrochloric acid and generate bubbles. Therefore, the higher the degree of oxidation of the sample and the thicker the oxide layer, the longer it will take for a large number of bubbles to appear in the hydrochloric acid solution. Figure 1 As shown, the time for bubbles to appear in each comparative example is longer than that in the corresponding embodiment, and most of the filler powder sinks to the bottom of the bottle or hangs in the bottle, indicating that the reaction is slower and the oxidation degree is higher.
[0076] In addition, the surface conductivity and magnetic shielding effectiveness of each embodiment are shown in the following table. Figure 2 , as shown in Table 2. It can be seen that due to the higher oxidation degree of each comparative example, the contact resistance between the core and the shell layer and between the particles is higher, the conductivity is lower, the eddy current loss is weaker, and the magnetic shielding effectiveness is weaker. It can be seen that the oxidation degree of each silver-coated magnetic metal filler prepared by the present invention is lower, the contact between the magnetic core and the conductive shell layer is closer, and it has excellent magnetic shielding effectiveness.
[0077] Table 2 Magnetic shielding effectiveness of Examples 1-2 and Comparative Examples 1-2
[0078] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a silver-coated magnetic metal filler having magnetic field shielding effectiveness, characterized in that: The following steps are involved: The magnetic metal powder is acid-washed to obtain acidified magnetic metal powder; The acidified magnetic metal powder is added to the silver nitrate solution, and then grease is added, followed by stirring and reacting to obtain the activated magnetic metal powder; The activated magnetic metal powder, reducing solution and silver ammonia solution are uniformly mixed, and then grease is added, and stirred to react to obtain a silver-coated magnetic metal filler with magnetic field shielding efficiency; The reducing liquid is prepared from a certain amount of dispersant, reducing agent and deionized water.
2. The method for preparing the silver-coated magnetic metal filler with magnetic field shielding effectiveness according to claim 1, characterized in that: The magnetic metal powder is one or more of iron-silicon-aluminum alloy, iron-silicon-chromium alloy, iron-silicon alloy, carbonyl iron, carbonyl nickel, iron-aluminum-boron alloy, iron-boron-phosphorus alloy, iron-nickel-molybdenum alloy, iron-chromium-nickel alloy, iron-nickel alloy, iron-cobalt-chromium alloy, and iron-cobalt-nickel-chromium alloy; The magnetic metal powder is spherical or flake in shape, and has a particle size of 4-42 μm.
3. The method for preparing the silver-coated magnetic metal filler with magnetic field shielding effectiveness according to claim 1, characterized in that: The silver nitrate solution is prepared by dissolving silver nitrate in a water solvent; The concentration of the silver nitrate solution is 0.5-10 g / L; The mass ratio of the acidified magnetic metal powder to silver nitrate is 10:0.1-3.
4. The method for preparing the silver-coated magnetic metal filler with magnetic field shielding effectiveness according to claim 1, characterized in that: During the preparation process of the activated magnetic metal powder, the reaction temperature is 30-45° C. and the reaction time is 0.5-3 h.
5. The method for preparing the silver-coated magnetic metal filler with magnetic field shielding effectiveness according to claim 1, characterized in that: The oil is one or more of cocoa butter, coconut oil, kerosene and paraffin oil.
6. The method for preparing the silver-coated magnetic metal filler with magnetic field shielding effectiveness according to claim 1, characterized in that: The dispersant is one or more of gelatin, polymethylpyrrolidone, OP-10, and sodium dodecylbenzene sulfonate; the reducing agent is one or more of glucose, formaldehyde solution, hydrazine hydrate, and potassium sodium tartrate.
7. The method for preparing the silver-coated magnetic metal filler with magnetic field shielding effectiveness according to claim 1, characterized in that: The silver ammonia solution is prepared by dispersing silver nitrate and ammonia water in a water solvent, wherein the concentration of the silver ammonia solution is 0.5-20 g / L, and the amount ratio of silver nitrate to ammonia water in the silver ammonia solution is 1:1.05-2.
8. The method for preparing the silver-coated magnetic metal filler with magnetic field shielding effectiveness according to claim 1, characterized in that: When the magnetic metal powder is pickled, it includes: Mix the magnetic metal powder with dilute sulfuric acid and stir for 2-6 minutes. Then use a magnet to adsorb the magnetic metal powder to the bottom of the container and pour out the supernatant. Wash the precipitate with deionized water until the pH of the supernatant is 6.5-7.
5. The concentration of the dilute sulfuric acid is 4-6wt%.
9. A silver-coated magnetic metal filler having magnetic field shielding effectiveness obtained by the method according to any one of claims 1 to 8.
10. Use of the silver-coated magnetic metal filler with magnetic field shielding effectiveness as claimed in claim 9 in electromagnetic shielding.
Citation Information
Patent Citations
Preparation method of Al-Ag alloy powder plated with silver chemically
CN102534585A
Preparation method of micro-structure controllable Ag / Al composite powder
CN118497729A
Ni-coated Ag core-shell type composite conductive powder and preparation method thereof
CN118983126A
Core-shell type composite conductive Fe-Ag filler and its prepn process
CN1974841A
Electroless gold plating method
JP1991162586A